PENGARUH PROFESIONALISME DAN GURU SERTA MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 1 KRADENAN - Rahayu, Titik (JI@P, 2015)
Titik Rahayu. 2015. âEffect of teacher professionalism, teacher performanceand student learning motivation toward the student learning achievement inState High School I (SMA Negeri 1) Kradenan. Slamet Riyadi University,Surakarta, Thesis, unpublished.This research aimed to find out (1) the effect of teacher professionalism onstudentsâ learning achievement, (2) the effect of teacher performance onstudentsâ learning motivation, (3) the effect of studentsâ learning motivationon learning achievement, and (4) the effect of teacher professionalism,teacher performance and studentsâ learning motivation on studentsâ learningachievement. The sample of research consisted of the graders of XI.IPA 1-3and XI.IPS 1-3 of SMA N 1 Kradenan, containing 60 respondents. Technique ofcollecting data used questionnaire through validity, reliability, and normalitytests. Technique of analyzing data used was path analysis, the combination ofcorrelation and regression, including product moment correlational, F- andmultiple regression tests. Research result indicated that (1) There is asignificant effect of teacher professionalism on studentsâ learningachievement, indicated by the correlation coefficient of 0.324 (low level ofrelationship) and p < 0.05. (2) There was a significant effect of teacherprofessionalism on studentsâ learning motivation, indicated by the correlationcoefficient of 0.317 (low level of relationship) and p < 0.05. (3) There was asignificant effect of teacher performance on studentsâ learning motivation,indicated by the correlation coefficient of 0.456 (medium level of relationship)and p < 0.05. (4) There was a significant effect of teacher performance onstudentsâ learning achievement, indicated by the correlational coefficient of0.314 (low level of relationship) and p < 0.05. (5) There was a significant effectof studentsâ learning motivation on learning achievement, indicated by thecorrelational coefficient of 0.643 (high level of relationship) and p < 0.05. (6)There was a significant effect of teacher professionalism, teacherperformance and studentsâ learning motivation simultaneously towardstudentsâ learning achievement, indicated by the multiple correlationcoefficient of 0.655 (high level of relationship) and p < 0.05. To improve thestudentsâ learning achievement in SMA N 1 Kradenan, the studentsâ learningmotivation should be improved supported by the improvement of teacherâsperformance and professionalism.Keywords: teacher professionalism, teacher performance, student learningmotivation, student learning achievement.